Pengaruh Corporate Governance Terhadap Firm Value Dengan Firm Age, Sales Growth, dan Leverage sebagai Variabel Kontrol: Studi Empiris pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2023 - Amalia Santika Putri; Erman Denny Arfinto (Faculty of Economics and Business Diponegoro University, 2026)
Firm value plays a central role in shaping investor perceptions and long-term corporate sustainability, making corporate governance an essential mechanism for ensuring managerial accountability and reducing agency conflicts. In emerging markets such as Indonesia, where transparency and governance quality remain uneven, the effectiveness of governance practices becomes even more crucial in strengthening market confidence. This study investigates how corporate governance, measured using Bloomberg’s Governance Pillar Score (Board Composition, Executive Compensation, Shareholder Rights, and Audit), influences firm value among companies listed in the LQ45 Index during 2019–2023. A total of 31 companies and 140 firm-year observations were selected using purposive sampling based on data obtained from the Bloomberg Database. The study uses unbalanced panel data, and the analysis was carried out using EViews 13 software. The findings show that Executive Compensation is the only governance indicator that has a positive and significant impact on firm value, highlighting the importance of aligning managerial incentives with shareholder interests. Meanwhile, Board Composition, Shareholder Rights, and Audit do not exhibit significant effects, suggesting that these governance dimensions may not yet contribute meaningfully to value creation in LQ45 companies. Overall, the results emphasize that performance-based compensation remains the most influential governance mechanism in shaping market valuation.